Pengaruh curing time dan pemanasan cetakan pasir kering terhadap kadar air, kuat tekan, dan lost of ignition (LOI) untuk aplikasi sand casting - Apang Shieddique; Dewi Maulidiawati; Moch Iqbal Muttahar; Irwan Suriaman (TURBO [Tulisan Riset Berbasis Online], 2022)
Sand molding has the advantage of being able to cast metals with high melting points, such as steel and nickel. Sand for the mold media generally uses a lot of silica sand. Some sand molds contain alphaset binders as well as other binders. Alphaset sand molding is a technique for making molds and metal casting cores that use resin as a binder and catalyst between sands. The addition of a catalyst as a mixture of resin. The process of making specimens for the sand mold test using silica sand SiO2 with a weight of 1000 g using 2.1% alphaphenolic resin and 25% catalyst from resin as additional elements for the resin hardening process. with a manual mixing process and making a sample with a diameter of 50mm in the form of a silencer with the tests carried out are water content, lost of ignition compressive strength and sand size distribution. Good moisture content data on alphaset molds are shown in temperature variations with heating. the results of testing the value of increasing compressive strength with variations in heating curing time 30, 60, 90 get results of 20.45, 22.8 and 31.85. data from the lost of ignition test sample curing time 30 get results of 2.05 The results of the distribution of sand are suitable for steel castings with large, medium and small sizes of castings, water content of curing time of 120, get results of more than 1%, namely 1.06 factors causing the mixin process. The above test shows an increase in compressive strength with variations in heating with lost of ignition testing temperature. The more often sand is used as the mold produces a higher LOI value.